Progress report on the crossbreeding programme between the Boer (Africander) and the East African Dwarf goats at Serere - Kyeyune-Sendagi, A.L. (1970)
A crossbreeding programme between an exotic goat breed (Boer) and the East African Dwarf Goat was initiated in the year 1965/66. The survivability of the Boer goats under Uganda conditions, as judged by severe experience, is very low. Kid mortality seems to be higher in the Boer crossbred kids (54.5%) than in the indigenous goats (33.3%). Boer crossbred kids of both sexes born of indigenous nanny-goats were heavier at birth (5.1lb) than the indigenous kids (3.9lb). The Boer crossbred male goats were faster growing at the age of twelve months (27.8lb) than all other types except the indigenous female goats (31.8lb) On the basis of preliminary data presented. It can be concluded that crossbreeding of Boar goats on the east African goats resulted in a faster growing progeny however extra care, must be given to the exotic goat breed in the breeding flocks.